Implementasi Tata Naskah Dinas Pada Kantor Kementerian Agama Kota Batam: - - 1 (Arsip Nasional Republik Indonesia, 2021)
In a government agency it is inseparable with the activities of creating archives in accordance with the implementation of functions, duties and responsibilities which include the activities of making archives and receiving archives as stated in Article 32 paragraph (1) of Government Regulation Number 28 of 2012 concerning Implementation of Law Number 43 2009 concerning Archives. Furthermore, in paragraph (2) it is stated that the creation and receipt of archives as referred to in paragraph (1) shall be carried out based on the official script administration, archive classification, as well as the security classification system and archive access. In order to create uniformity in the creation of archives, especially official manuscripts, the Ministry of Religion of the Republic of Indonesia in this case as a vertical agency of the Ministry of Religion has issued a policy, namely the Decree of the Minister of Religion Number 9 of 2016 concerning Guidelines for Official Manuscripts at the Ministry of Religion. This study aims to assess the suitability between the official script system in making official letters implemented in the Batam City Ministry of Religion Office and the factors that influence it. The work units that are the source of this research are the Ministry of Religion Office Unit per work unit, the Subdistrict Religious Affairs Office work unit, and the Public Madrasah work unit within the Batam City Ministry of Religion Office. This research uses descriptive method and how to obtain data is by observation and documentation. Testing the validity of the data in this study using triangulation. The results obtained indicate that not all work units within the Ministry of Religion Office are in accordance with KMA No. 9/2016. influencing mismatches in the implementation of the official script administration, including position code and archive classification, employee competence, monitoring and evaluation, leadership commitment, and habits.